Co-processing of fossil feedstock with lignin-derived model compound isoeugenol over Fe-Ni/H-Y-5.1 catalysts - Vajglova Zuzana; Gauli Bibesh; Mäki-Arvela Päivi; Simakova Irina L.; Kumar Narendra; Eränen Kari; Tirri Teija; Lassfolk Robert; Peurla Markus; Doronkin Dmitry E.; Murzin Dmitry Yu (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2025)
Co-processing of n-hexadecane with lignin derived isoeugenol as a model compound was investigated in this work using low-cost mono-and bimetallic iron and nickel supported on H-Y-5.1 zeolite. Different Fe-Ni metal ratios in the catalyst led to different reaction rates of processes and product distribution. The presence of just 0.26 wt% isoeugenol in the mixture with n-hexadecane made hydroisomerization-hydro cracking of the latter two-fold less active. Catalysts with smaller metal particle sizes, lower than 6 nm were more efficient pointing out on structure sensitivity. Extremely high activity in co-processing was obtained over 2 wt% Fe - 8 wt% Ni/H-Y-5.1 catalysts with the median metal particle size of 4.6 nm and metals-to-acid site ratio of 8.6. Fe catalyst were much less active in isoeugenol hydrodeoxygenation, while high cracking activity of hexadecane was observed in the presence of Ni. Alkylation of n-hexadecane was a feature of 8 wt% Fe - 2 wt% Ni/H-Y-5.1, whereas, over the 5 wt% Fe - 5 wt% Ni/H-Y-5.1 bifunctional catalyst no undesired oxygen-containing cyclic products were detected. This catalyst exhibited the highest hydrogen consumption according to temperature programmed desorption, which can serve as a marker for efficient hydrodeoxygenation. The spent catalysts contained ca 40 wt% of coke with predominantly aliphatic species. (c) 2023 The Author(s). Published by Elsevier Inc. This is an open access article under the CC BY license (http://creativecommons.org/licenses/by/4.0/).